Evolution and contemporary landscape of neonatal hyperbilirubinemia management guidelines: a narrative review - Zhang, Yaxin; Zhang, Yaowen; Huang, Qin; Yi, Shuhua; Guan, Xiaoqing; Li, Hongyu; He, Jun (Frontiers in Pediatrics, 2026)
Neonatal hyperbilirubinemia, affecting over 60% of term and 80% of preterm infants globally, remains a significant public health challenge due to the persistent risk of kernicterus despite effective management strategies. This narrative review summarizes global clinical practice guidelines to describe the evolution and current landscape of management, highlighting the disparity between evidence-based consensus and local adaptation. While universal principles such as early hyperbilirubinemia screening, phototherapy as the first-line treatment, and post-discharge follow-up are widely endorsed, substantial disparities exist in implementation—particularly between high-income countries and low- and middle-income countries (LMICs)—driven by differences in healthcare resources, sociocultural perceptions, and technological access. The 2025 Chinese guideline is an integrated model combining risk-stratified screening, locally derived hour-specific nomograms, online follow-up, and family engagement, offering a scalable framework for LMICs. Looking ahead, global harmonization may require a dual-layered guideline structure, affordable technology dissemination, culturally adapted family support systems, and inclusion of hyperbilirubinemia metrics in national health performance evaluations to achieve equitable and effective care worldwide.